Pengaruh Literasi Media dan Mindful Social Media Use terhadap Self-Esteem pada Generasi Z di Kota Medan - Chairunnisah Rahmi Nasution; Iskandar Zulkarnain; Emilia Ramadhani (KOLONI, 2026)
This study aims to analyze the influence of media literacy and mindful social media use on self-esteem among Generation Z in Medan City. This research employed an explanatory quantitative approach within a positivist paradigm. Data were collected through an online questionnaire distributed to 400 active social media users from Generation Z and analyzed using multiple linear regression with IBM SPSS Statistics 29. The research instrument used a four-point Likert scale and demonstrated reliability through Cronbach Alpha values of 0.903 for media literacy, 0.806 for mindful social media use, and 0.905 for self-esteem. The results show that media literacy has a positive and significant effect on self-esteem, with t = 4.218 and p < 0.001. Mindful social media use also has a positive and significant effect on self-esteem, with t = 4.397 and p < 0.001. Simultaneously, both variables significantly influence self-esteem, with F = 30.302, p < 0.001, and R² = 0.132. These findings indicate that the ability to critically understand media information and use social media consciously serves as a protective factor in maintaining Generation Z’s self-evaluation amid the pressure of digital social validation.